Effectiveness of proposed models in designing electronic accounting information systems to enhance the quality of financial reports - Mustafa, Zanyar Najmuddin Mustafa; Ahmed, Prof.Dr.Razgar Ali Ahmed (Sulaimani Journal for Humanities, 2026)
The purpose of this study is to analyze the impact of the designed models on the electronic accounting information systems which improve the quality of the financial reports. The models are intended to improve the digital accounting systems as to the effective and precise processing of accounting information. These also assist in the consolidation and universal access to information which minimizes the probability of errors committed by a person. The models provide precise and timely reports which enhances the financial reports and supports the decision-making process in the institution. These systems improve internal controls as well. The models designed digital systems which are developed based on contemporary challenges of the paper systems. The designed models improve the value of the financial reports to the institution by increasing the transparency and the reliability of the reports. Thus, the study suggests that these models should be included in the institutions digital transformation initiatives to achieve improved financial and accounting results
Keywords: Electronic information systems; financial reporting quality; digital transformation; financial performance